2022
DOI: 10.3390/molecules27030862
|View full text |Cite
|
Sign up to set email alerts
|

A New Butyrate Releaser Exerts a Protective Action against SARS-CoV-2 Infection in Human Intestine

Abstract: Butyrate is a major gut microbiome metabolite that regulates several defense mechanisms against infectious diseases. Alterations in the gut microbiome, leading to reduced butyrate production, have been reported in patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. A new butyrate releaser, useful for all the known applications of butyrate, presenting physiochemical characteristics suitable for easy oral administration, (N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA), has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Both propionate and butanoate showed a similar increase of E-cadherin expression and EMT inhibiting features from our in vitro study, and both are in clinical trials for various conditions like diabetes, obesity, inflammatory bowel disease and end stage renal disease. However, butanoate’s suitability in the clinical and nutrition context is limited due to its unpleasant odor and rapid absorption rate in the upper gastrointestinal tract [41,42], while propionate is a safe food ingredient with clinical benefits [43]. Therefore, we decided to focus more towards propionate’s role in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Both propionate and butanoate showed a similar increase of E-cadherin expression and EMT inhibiting features from our in vitro study, and both are in clinical trials for various conditions like diabetes, obesity, inflammatory bowel disease and end stage renal disease. However, butanoate’s suitability in the clinical and nutrition context is limited due to its unpleasant odor and rapid absorption rate in the upper gastrointestinal tract [41,42], while propionate is a safe food ingredient with clinical benefits [43]. Therefore, we decided to focus more towards propionate’s role in lung cancer.…”
Section: Resultsmentioning
confidence: 99%
“…25,26,28,40,52,53 In 2022, 18 studies used a traditional non-targeted metabolomics assay. 18,24,30,[83][84][85][86][87][88][89][90][91][92][93][94][95][96][97] Perhaps the most thought-provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature. This study identified an exercise-induced metabolite, namely N-lactoylphenylalanine (Lac-Phe), to be associated with reduced dietary intake.…”
Section: Metabolomicsmentioning
confidence: 99%
“…In 2022, 18 studies used a traditional non‐targeted metabolomics assay 18,24,30,83–97 . Perhaps the most thought‐provoking exercise metabolomics publication from 2022 came from the Long Lab at Stanford University and was published in Nature .…”
Section: Analytical Approaches For Ms‐based Investigations In Ses In ...mentioning
confidence: 99%
“…Depletion of SCFA synthesis pathways was associated with disease severity and showed persistent depletion in patients even after viral clearance ( 82 ). Furthermore, a recently published study investigating the role of butyrate releaser (N-(1-carbamoyl-2-phenyl-ethyl) butyramide (FBA) showed promising results in modulating the expression of ACE2, TMPRSS2, and inflammatory cytokines IL-15, MCP-1 and TNF-α in intestinal biopsies ( 83 ). SCFAs are also play important role in strengthening intestinal barrier function, regulating inflammation and oxidative stress in intestinal epithelial cells ( 84 ).…”
Section: Gut Microbial Alterations In Oud and Sars-cov-2 Infectionmentioning
confidence: 99%